2015
DOI: 10.1055/s-0034-1387686
|View full text |Cite
|
Sign up to set email alerts
|

Selbstmanagementförderung in der hausärztlichen Versorgung – der Zusammenhang zwischen Veränderungsmotivation, Selbstwirksamkeit und psychischer Belastung vor Beginn der Intervention

Abstract: Anxiety, depressive and somatoform disorders are highly prevalent in primary care. Managing these disorders is time-consuming and requires strong commitment on behalf of the general practitioners (GPs). Furthermore, the resources for the management of these patients are limited by the increasing workload in primary care practices, especially in the German health care system. In order to address the SMADS-study within psychenet - the Hamburg Network for Mental Health (NCT01726387) implements and evaluates a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
2
Order By: Relevance
“…Although patients' motivation for change and their perceived self-efficacy are not well studied to date [ 40 ], we demonstrated that PD patients were able and willing to learn stress management techniques for 2 hours weekly over 8 weeks and accept SMT as chance to lower disease-related stress factors and symptoms. In accordance, none of the PD patients finished SMT prematurely (in contrast to controls).…”
Section: Discussionmentioning
confidence: 90%
“…Although patients' motivation for change and their perceived self-efficacy are not well studied to date [ 40 ], we demonstrated that PD patients were able and willing to learn stress management techniques for 2 hours weekly over 8 weeks and accept SMT as chance to lower disease-related stress factors and symptoms. In accordance, none of the PD patients finished SMT prematurely (in contrast to controls).…”
Section: Discussionmentioning
confidence: 90%
“…Die ersten fünf Teilprojekte sollten krankheitsübergreifend die Aufklärung über und Entstigmatisierung von psychischen Erkrankungen fördern , den Zugang zu qualitätsgesicherten und evidenzbasierten Informationen zu psychischen Erkrankungen, Screeningmaßnahmen, Entscheidungshilfen und die Hilfesuche durch die Implementierung einer Website verbessern (Dirmaier et al 2015). Außerdem sollten die betriebliche Gesundheit durch eine multimodale Intervention in Betrieben unterstützt (Toska et al 2015), die Diagnostik und Indikationsstellung in der hausärztlichen Primärversorgung verbessert (Zimmermann et al 2015) und die Beteiligung von Betroffenen und Angehörigen durch eine »Peer-to-Peer«-Beratung gefördert werden (Mahlke et al 2015). Zudem wurden fünf krankheitsspezifische sogenannte Gesundheitsnetze für die folgenden Erkrankungen konzipiert: unipolare Depression (Heddaeus et al 2015), Psychosen (Lambert, Schöttle et al 2015), Suchterkrankungen im Jugendalter (Arnaud et al 2015), Essstörungen (Weigel et al 2015) In den Interviews mit Netzwerkpartnerinnen und -partnern herrschten bezüglich der Funktionsfähigkeit unterschiedliche Meinungen vor.…”
Section: Realisierung Von Psychenetunclassified
“…Ansätze, die das Selbstmanagement der Betroffenen unterstützen, gelten international mittlerweile als evidenzbasiert [35]. Entsprechende Programme zielen auf informierte Entscheidungsfindung, Adhärenz, gezielte Rückfallprävention und Problemmanagement [36]. Die wissenschaftliche Evidenz zu Ansätzen der Peer-Arbeit ist vielversprechend [37].…”
Section: Abstract !unclassified